87 The role of simulation and transfer training in anaesthesia. (17th November 2016) - Martin, Rebecca; Shirley, P; Mitchell, D; Tarrell, T
Abstract : Introduction: Transferring a critically ill patient often falls to a junior anaesthetist. It is estimated that over 11000 transfers occur annually in the UK and this figure is set to rise with continued centralisation of services to tertiary centres. The RCOA, AAGBI and FICM state that staff transporting critically ill patients should receive competency specific training and gain experience in a supernumerary capacity. This aspiration is difficult to attain due to staffing limitations and the out-of-hours nature of the work. A lack of non-technical skills can contribute to transfer-associated critical incidents and therefore the integration of simulation into transfer courses is important, but in the author's opinion, not always a component of current transfer training courses. Method: We conducted an email survey across Barts and the London School of Anaesthesia to establish training level and experience in transfer medicine. We established how competency was achieved, the type of critical incidents encountered, and questioned what candidates wanted most from a transfer course. Results: A large proportion of trainee Anaesthetists not only lack formal training in transfer medicine but 46% (7/15) admit to "sometimes" and 6% (1/15) "always" feel out-of-their-depth during transfer of critically ill patients. Forty per cent (6/15) have never been supervised on a transfer and yet 60% (9/15) have performed more than 5 solo transfers. Equipment/monitoring failure, poorly trained assistance and patient deterioration appear to be the most commonly encountered critical incidents. Conclusion: A formal 1-day workshop and simulation course focused at CT1/2 level will help to develop confidence in technical and non-technical skills necessary for safe transfer of the critically ill. As the course is standardised to follow the RCOA curriculum, work-place based assessments can be awarded to those displaying competence during simulations and in a final MCQ as determined by the College Tutor and Lead Transfer Consultant.